2010
DOI: 10.1093/molbev/msq337
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics of Transposable Elements in Drosophila melanogaster

Abstract: Transposable elements (TEs) are the primary contributors to the genome bulk in many organisms and are major players in genome evolution. A clear and thorough understanding of the population dynamics of TEs is therefore essential for full comprehension of the eukaryotic genome evolution and function. Although TEs in Drosophila melanogaster have received much attention, population dynamics of most TE families in this species remains entirely unexplored. It is not clear whether the same population processes can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
215
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(235 citation statements)
references
References 73 publications
18
215
1
1
Order By: Relevance
“…To explore the evolutionary implications of our observations, we used existing data (Petrov et al 2011) on the population frequencies of many transposons, including 56 of the TSCbearing insertions we identified (Methods; Supplemental Table S6). Of those insertions, 45 are estimated to be rare or very rare variants in the wild North-American (NA) populations studied.…”
Section: Population Genetics Of Transposon-derived Genic Tscsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the evolutionary implications of our observations, we used existing data (Petrov et al 2011) on the population frequencies of many transposons, including 56 of the TSCbearing insertions we identified (Methods; Supplemental Table S6). Of those insertions, 45 are estimated to be rare or very rare variants in the wild North-American (NA) populations studied.…”
Section: Population Genetics Of Transposon-derived Genic Tscsmentioning
confidence: 99%
“…We used the genotyping data for FlyBase-annotated transposon insertions from Petrov et al (2011). Each transposon-contained TSC was attributed to a FlyBase transposon annotation if it fully overlapped one of them (108 insertions).…”
Section: Population Genetics Data Analysismentioning
confidence: 99%
“…These lower estimates, however, do not include the possible presence in natural populations of genotypes with high mutation rates or the deleterious consequences of transposable element (TE) insertions. In fact, TEs are very abundant in natural populations of D. melanogaster [51][52][53][54][55][56][57][58][59][60] and have been proposed to be an important source of BGS in this species [30]. Therefore, U,0.6 represents a lower boundary for the deleterious mutation rate when inferring the consequences of BGS.…”
mentioning
confidence: 99%
“…TEs are pervasive across the D. melanogaster genome [51][52][53][54][55][56][57][58][59][60]. Cridland et al (2013) recently reported a detailed analysis of TE abundance and distribution in D. melanogaster based on deepcoverage, whole-genome sequencing [60].…”
mentioning
confidence: 99%
“…TE propagation rates can be inferred from comparative phylogenetic analyses of related organisms (14)(15)(16)(17)(18)(19)(20) or endpoint analyses of TE abundance within populations (11,(21)(22)(23). By making assumptions about the mechanisms of TE proliferation, models can be constructed to describe the distribution of TEs within genomes over evolutionary time scales, and sequenced genomes can be analyzed and fit to TE proliferation models to infer phylogeny of TE copies and estimate their rates of propagation (24).…”
mentioning
confidence: 99%